Effect of the spatial–temporal specific theca cell Cyp17 overexpression on the reproductive phenotype of the novel TC17 mouse - Secchi, Christian; Belli, Martina; Harrison, Tracy N. H.; Swift, Joseph; Ko, CheMyong; Duleba, Antoni J.; Stupack, Dwayne; Chang, R. Jeffrey; Shimasaki, Shunichi (Journal of translational medicine, 2021)
In the ovarian follicle, the Theca Cells (TCs) have two main functions: preserving morphological integrity and, importantly, secreting steroid androgen hormones. TCs express the essential enzyme 17α-hydroxylase/17,20-desmolase (CYP17), which permits the conversion of pregnenolone and progesterone into androgens. Dysregulation of CYP17 enzyme activity due to an intrinsic ovarian defect is hypothesized to be a cause of hyperandrogenism in women. Androgen excess is observed in women with polycystic ovary syndrome (PCOS) resulting from excess endogenous androgen production, and in transgender males undergoing exogenous testosterone therapy after female sex assignment at birth. However, the molecular and morphological effects of Cyp17 overexpression and androgen excess on folliculogenesis is unknown. In this work, seeking a comprehensive profiling of the local outcomes of the androgen excess in the ovary, we generated a transgenic mouse model (TC17) with doxycycline (Dox)-induced Cyp17 overexpression in a local and temporal manner. TC17 mice were obtained by a combination of the Tet-dependent expression system and the Cre/LoxP gene control system. Ovaries of Dox-treated TC17 mice overexpressed Cyp17 specifically in TCs, inducing high testosterone levels. Surprisingly, TC17 ovarian morphology resembled the human ovarian features of testosterone-treated transgender men (partially impaired folliculogenesis, hypertrophic or luteinized stromal cells, atretic follicles, and collapsed clusters). We additionally assessed TC17 fertility denoting a perturbation of the normal reproductive functions (e.g., low pregnancy rate and numbers of pups per litter). Finally, RNAseq analysis permitted us to identify dysregulated genes (Lhcgr, Fshr, Runx1) and pathways (Extra Cellular Matrix and Steroid Synthesis). Our novel mouse model is a versatile tool to provide innovative insights into study the effects of Cyp17 overexpression and hyperandrogenism in the ovary.